2020
DOI: 10.1016/j.jcrimjus.2020.101729
|View full text |Cite
|
Sign up to set email alerts
|

Untangling sexual homicide: A proposal for a new classification of sexually motivated killings

Abstract: Purpose: The study aimed to develop an empirically driven checklist guiding clinicians in the decision-making process that would enable them to determine the functional role of the killing in a newly proposed classification of sexual homicides.Methods: Classical Test Theory, Exploratory Factor Analyses and Two-parameter item response theory were conducted on a sample of 361 male sexual killers assigned as either belonging to the direct or indirect group.Results: The results revealed that an eight-item checklis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 27 publications
(51 reference statements)
0
21
0
Order By: Relevance
“…Female victims are more at risk in the context of pending estrangement, when they are trying to leave or have recently ended the relationship, increasing the likelihood of IPH of female victims by over two times (Spencer & Stith, 2020). Interestingly, meta-analyses also suggested that previous 6 use of non-fatal strangulation, homicide ideation and threats as well as stalking significantly increase the chances of assaults leading to homicide (Matias et al, 2020;Spencer & Stith, 2020) indicating that perhaps lethal acts might not have been as spontaneous as they appeared (Stefanska et al, 2020). Interestingly, Spencer and Stith (2020) also noted that the risk of homicide increased if the perpetrator forced sex on the victim.…”
Section: Motivationmentioning
confidence: 99%
“…Female victims are more at risk in the context of pending estrangement, when they are trying to leave or have recently ended the relationship, increasing the likelihood of IPH of female victims by over two times (Spencer & Stith, 2020). Interestingly, meta-analyses also suggested that previous 6 use of non-fatal strangulation, homicide ideation and threats as well as stalking significantly increase the chances of assaults leading to homicide (Matias et al, 2020;Spencer & Stith, 2020) indicating that perhaps lethal acts might not have been as spontaneous as they appeared (Stefanska et al, 2020). Interestingly, Spencer and Stith (2020) also noted that the risk of homicide increased if the perpetrator forced sex on the victim.…”
Section: Motivationmentioning
confidence: 99%
“…However, ignoring balanced sampling most likely affected the conclusions drawn. Stefanska et al 2020 highlighted that if the sample was over-represented by serial cases, the results might have indicated a higher prevalence of characteristics mainly related to serial offenders for example sadistic tendencies. The authors further argued that in depth analysis of non-serial offenders (or adhering to balanced sampling) is crucial as it would deliver much needed research-based evidence guiding professionals in their working practices.…”
Section: Serial Vs Non-serial Sexual Homicidementioning
confidence: 99%
“…It also often requires reliance on the perpetrator's disclosure which may not be accurate within forensic settings, especially when the person committed a violent attack. This issue has been highlighted in relation to determining sadism as the main source of sexual excitement (Nitschke et al, 2013) as well as assessing perpetrator's other emotional states, for example, anger (Stefanska et al, 2020). Marshall et al (2002) showed that imprecise diagnostic criteria, which allow for subjective assessment, impact on diagnostic reliability.…”
Section: Cognitive Statementioning
confidence: 99%
See 2 more Smart Citations